Phytochemical Studies on Pteris excelsa - Shi, X.B.; Xie, Q.H.; Duan, A.H.; He, F.; Chen, Y.G. (Asian Journal of Chemistry, 2011)
Present study reports the chemical constituents of Pteris excelsa Gaud. The compounds were isolated by MCI gel chromatography and silica gel column chromatography. Their structures were identified by physicochemical properties and spectroscopic analysis. Three compounds were elucidated as luteolin 7-O-b-D-glucoside (1), b-sitosterol (2) and fructose (3). All the compounds were isolated from Pteris excelsa Gaud for the first time.